Clinical dermatology - Soutor, Carol; Hordinsky, Maria K. (Lange Medical Books/McGraw-Hill, 2013)
This book is about practical and up-to-date information on presentation, differential diagnosis, laboratory evaluation, pathology findings, and therapy for 100 of the most commonly encountered skin diseases make this as an excellent dermatology reference for clinicians.